2014
DOI: 10.4238/2014.september.29.4
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of miR-122 and miR-29 in hepatitis B virus-related liver disease

Abstract: ABSTRACT. MicroRNA molecules have been increasingly regarded as a diagnostic and prognostic marker of certain diseases. The aim of this study was to investigate the expression and clinical significance of miR-122 and miR-29 in liver disease related to hepatitis B virus infection. The serum levels of miR-122 and miR-29 in 20 patients with hepatocellular carcinoma (HCC), 20 patients with liver cirrhosis (LC), 29 patients with chronic hepatitis B (CHB), 20 cases of hepatitis B virus carriers (ASC), and 20 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
3
19
0
1
Order By: Relevance
“…13 associated with chronic HBV infection [106]. In addition, miR-29b was involved in the hypomethylation of PTEN by curcumin.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…13 associated with chronic HBV infection [106]. In addition, miR-29b was involved in the hypomethylation of PTEN by curcumin.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These miRNAs exhibit a consistent expression profile among healthy individuals. miR-122, the most abundant hepatic microRNA, has been evaluated mainly in chronic hepatitis B virus (HBV), hepatitis C virus (HCV) infections and hepatocellular carcinoma (HCC) [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Roderburg et al analyzed serum miR‐122 expression in 223 patients with critical illness and 57 with cirrhosis, demonstrating that an elevated serum miR‐122 level was an independent marker of ongoing liver injury regardless of the underlying disease. As miR‐122 is correlated with liver damage in chronic hepatitis B (CHB) patients, it can be employed as a potential biomarker for the evaluation of CHB . In vitro studies have shown that miR‐122 could inhibit HBV replication .…”
Section: Introductionmentioning
confidence: 99%
“…As miR-122 is correlated with liver damage in chronic hepatitis B (CHB) patients, 17 it can be employed as a potential biomarker for the evaluation of CHB. 17,18 In vitro studies have shown that miR-122 could inhibit HBV replication. 19 In China, CHB-related liver failure (CHBLF) has extremely high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%